APPLICATION OF QUALITY PLANNING TO OPTIMIZE PRODUCT AND CONSTRUCTION PROJECT QUALITY - Nguyen Anh, Tuan; Le Manh, Tuong; Huynh Van, Tung (Journal of Applied Engineering Science, 2021)
A country is called developed when the capacity and progress of science and technology have created products that always meet the requirements and increasing needs of people, ensuring stability and development of the nation in particular and the movement of the world in general. In Vietnam, the quality of goods is still modest. This exists not only from a macro perspective but also from a micro perspective and the transition from macro to micro because of a lack of orientation, or can be called the lack of "Product quality planning” [21,25] in terms of space. This paper will discuss the concepts of quality, expand the concept of quality with the aim of achieving good quality, meeting increasing requirements, need to perform the "quality planning" work under the space degree. The paper uses a mathematical tool based on the Cartesian coordinate system to determine the optimal value of product quality in order to demonstrate quantitatively according to the spatial frameworks when the quality is desired to achieve the required perfection through the magnitude of the "quality demand.” In a similar way, in order to get the construction project achieve the maximum quality, there must be adjustment solutions in 3 aspects. However, at present, in Vietnam in particular and the world in general, there have not been many in-depth studies on the formation of quality and the factors affecting the quality, especially the industrial construction projects [3]. Through the success or failure of investment projects in the form of public private partnerships (PPP) of countries around the world, including developed countries, the author thinks that in order for the project to be successful, it is necessary to apply construction product quality planning.
Keywords: Product quality; quality planning; quality demand; satisfaction level; optimal values